Implementation of The School Literacy Movement in One of Elementary School in Bandung - Nabilah, Annisa; Hartati, Tatat (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2024)
This research aims to describe the implementation of the School Literacy Movement (SLM) program in one of the elementary schools in the city of Bandung. The School Literacy Movement (SLM) program is an effort to make all school residents into literate human resources, as stated in Ministerial Regulation Number 23rd of 2015 concerning Moral Development, which includes habituation to a literacy culture. This study used descriptive qualitative method. The instruments used were interview guides, observation guidelines and learning documentation guidelines. The research results show that the implementation of the SLM program in this school has not been implemented optimally because there are still several obstacles that have not been resolved so that it has not had a positive impact on students' interest in reading and literacy skills. This is indicated by the lack of student reading activity during learning in the school environment and the lack of adequate facilities, infrastructure and facilities.